Active chloride cell density in some tissues of rainbow trout (Oncorhynchus mykiss Walbaum, 1792) larvae during the early development stage - Çalta, M (Polish Acad of Sciences, 2002)
In this study, active chloride cell density in some tissues (gill arch epithelium, skin, and yolk-sac membrane) of rainbow trout (Oncorhynchus mykiss Walbaum, 1792) larvae during the early development stage was investigated using a vital fluorescence staining technique. It was found that the numbers of active chloride cells were very variable, depending on the tissue and age of the larvae. Active chloride cells were most abundant in the skin and yolk-sac membrane, but less so in the gill arch epithelium of newly hatched larvae. With larval age, the density of active chloride cells in the gill epithelium increased, while that in the skin and yolk-sac membrane decreased.
Keywords: chloride cell; rainbow trout; Oncorhynchus mykiss; gill; skin; yolk-sac